THE DEGREE OF JUICINESS AND CHEMICAL COMPOSITION OF SORGHUM SEEDS - Qurbonov Fazliddin Nuriddinovich; Shomurotova Nargiza Qarshievna (Academia Science Repository, 2023)
The article presents the information obtained about the moisture content and the chemical composition of the seed in corn varieties. It shows that the value of the indicators of the moisture level and the chemical composition of the seed is directly related to the conditions of their cultivation, soil and climate factors. Also, the value of these indicators has changed to different degrees directly depending on the biological characteristics of the varieties and their properties of resistance to stress factors.